HIV Viral Load Scale-up Among Children and Adolescents: Trends in Viral Load Suppression, Sample Type and Processing in 7 PEPFAR Countries, 2015–2018. Issue 4 (18th January 2023) - Hrapcak, Susan; Pals, Sherri; Itoh, Megumi; Peters, Natalie; Carpenter, Deborah; Hackett, Stephanie; Prao, Aka K.; Adje-Toure, Christiane; Eboi, Ehui; Mutisya, Immaculate; Nyabiage Omoto, Lennah; Ondondo, Raphael O.; et al.
Abstract : HIV-positive children and adolescents face gaps in viral load (VL) testing. To understand trends in pediatric/adolescent VL testing, 7 countries collected data from Laboratory Information Management Systems. Results showed increasing proportion of VL tests done through dried blood spot (DBS) and decreased sample rejection rates for DBS compared with plasma, supporting use of DBS VL when skilled phlebotomy is unavailable.